PENERAPAN METODE PEMBELAJARAN TUTOR SEBAYA DENGAN BANTUAN QUESTION CARD UNTUK MENGEMBANGKAN AKTIVITAS BELAJAR SISWA SMP KELAS VIII - Purwati, Fita; Khanafiyah, Siti; Sarwi, Sarwi (UPEJ Unnes Physics Education Journal, 2017)
The purpose of this research were implementation peer tutor learning method to develop students' learning activities and determine the magnitude of the development student activity after implemented peer tutor learning method helped by question cards. The research design used Quasi Experiment with the form Pretest-Posttest Group. The instrument of this research used observation sheets to determine the development of students' learning activities. The results of this research stated that students' learning activity is low after implementation of peer tutor learning helped by question cards. The gain score of concept understanding was 0,52 which include moderate category.